Latitudinal distributions of particulate carbon export across the North Western Atlantic Ocean. (November 2017) - Puigcorbé, Viena; Roca-Martí, Montserrat; Masqué, Pere; Benitez-Nelson, Claudia; Rutgers van der Loeff, Michiel; Bracher, Astrid; Moreau, Sebastien
Abstract: 234 Th-derived carbon export fluxes were measured in the Atlantic Ocean under the GEOTRACES framework to evaluate basin-scale export variability. Here, we present the results from the northern half of the GA02 transect, spanning from the equator to 64°N. As a result of limited site-specific C/ 234 Th ratio measurements, we further combined our data with previous work to develop a basin wide C/ 234 Th ratio depth curve. While the magnitude of organic carbon fluxes varied depending on the C/ 234 Th ratio used, latitudinal trends were similar, with sizeable and variable organic carbon export fluxes occurring at high latitudes and low to negligible fluxes occurring in oligotrophic waters. Our results agree with previous studies, except at the boundaries between domains, where fluxes were relatively enhanced. Three different models were used to obtain satellite-derived net primary production (NPP). In general, NPP estimates had similar trends along the transect, but there were significant differences in the absolute magnitude depending on the model used. Nevertheless, organic carbon export efficiencies were generally < 25%, with the exception of a few stations located in the transition area between the riverine and the oligotrophic domains and between the oligotrophic and the temperate domains. Satellite-derived organic carbon export models fromDunne et al. (2005) (D05), Laws et al. (2011) (L11) andHenson et al. (2011) (H11) were also compared to our 234 Th-derived carbon exports fluxes. D05 and L11 provided estimates closest to values obtained with the 234 Th approach (within a 3-fold difference), but with no clear trends. The H11 model, on the other hand, consistently provided lower export estimates. The large increase in export data in the Atlantic Ocean derived from the GEOTRACES Program, combined with satellite observations and modeling efforts continue to improve the estimates of carbon export in this ocean basin and therefore reduce uncertainty in the global carbon budget. However, our results also suggest that tuning export models and including biological parameters at a regional scale is necessary for improving satellite-modeling efforts and providing export estimates that are more representative of in situ observations.